(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the effect of light quality and the plant growth regulators 2-isopentenyl adenine (2-ip) and indol 3-butyric acid (IBA) on in vitro multiplication and rooting of ‘Woodard’ blueberry. The experiments were arranged in a completely randomized design, with three light quality levels (red, blue, and white), and two plant growth regulator levels (presence or absence of either 100 mg L-1 2-ip or 0.5 mg L-1 IBA, in the multiplication and rooting experiments, respectively). The parameters assessed in both experiments were survival rate (%), number of shoots per explants shoot length (cm); number of leaves per explant, and leaf area (cm2). In the multiplication experiment was also quantified the photosynthetic pigments contents [chlorophyll (chl) a and chl b, chl a + b, and carotenoids] and in the rooting trial the root number and length. The results show that the presence of 2-ip in association with white light results in longer shoots, as well as greater number of shoots and leaves. The greastest leaf area was observed with white light. Root number and length was greater in the presence of IBA in the medium. The association of white fluorescent light and the presence of either 2-isopentenyl adenine (2-ip) or indole 3-butyric acid (IBA) in the medium, provides the best results for in vitro multiplication and rooting, respectively, of ‘Woodard’ blueberry.